Social care‐related outcomes in Finland. Construct validity and structural characteristics of the Finnish ASCOT measure with older home care users. (27th February 2021) - Nguyen, Lien; Linnosmaa, Ismo; Jokimäki, Hanna; Rand, Stacey; Malley, Juliette; Razik, Kamilla; Trukeschitz, Birgit; Forder, Julien
Abstract: The Adult Social Care Outcomes Toolkit four response‐level interview schedule (ASCOT INT4) for service users was translated into Finnish. The aim of this paper was to investigate the construct validity and structural characteristics of the Finnish ASCOT. We used data from a face‐to‐face interview survey of older people receiving publicly funded home care services, which was conducted in 2016–2017 ( n = 493), excluding missing values and proxy respondents ( n = 334). Chi‐square tests, adjusted residuals and analyses of variance were used to examine hypothesised associations between each attribute and a number of relevant variables regarding health and well‐being, disabilities, living arrangements, social contact and support, experience of service use, and the nature of the locality and environment. Structural characteristics were explored using exploratory factor analysis and Cronbach's alpha test. The EQ‐5D‐3L and ASCOT were moderately correlated (r = 0.429; p < 0.001). The ASCOT attributes were statistically positively related to the overall quality of life. For other tested variables, we found a high number of significant associations with the control over daily life, occupation, social participation, and personal cleanliness attributes, but fewer significant associations with the other attributes. Cronbach's alpha was 0.697 and a single factor was extracted. This assessment provides evidence to support the construct validity of the Finnish ASCOT. The results support the introduction of the Finnish ASCOT into Finland for use in practical applications. Future research on its reliability would be useful.